2013
DOI: 10.1038/cdd.2013.16
|View full text |Cite
|
Sign up to set email alerts
|

The loss of the BH3-only Bcl-2 family member Bid delays T-cell leukemogenesis in Atm−/− mice

Abstract: Multicellular organisms maintain genomic integrity and resist tumorigenesis through a tightly regulated DNA damage response (DDR) that prevents propagation of deleterious mutations either through DNA repair or programmed cell death. An impaired DDR leads to tumorigenesis that is accelerated when programmed cell death is prevented. Loss of the ATM (ataxia telangiectasia mutated)-mediated DDR in mice results in T-cell leukemia driven by accumulation of DNA damage accrued during normal T-cell development. Pro-apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
(59 reference statements)
3
18
0
Order By: Relevance
“…Consequently, proapoptotic molecules are supposed to induce apoptosis and prevent tumor development. Contrary to this expectation, two previous studies with independent mouse models showed that loss of proapoptotic BID delays tumor development . In line with these findings, loss of BID significantly delayed tumor development after Fah ‐mediated and HBsTg ‐driven chronic injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, proapoptotic molecules are supposed to induce apoptosis and prevent tumor development. Contrary to this expectation, two previous studies with independent mouse models showed that loss of proapoptotic BID delays tumor development . In line with these findings, loss of BID significantly delayed tumor development after Fah ‐mediated and HBsTg ‐driven chronic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with the carcinogen DEN significantly delayed tumor development in Bid −/− mice, which was attributed to impaired hepatocyte proliferation . Moreover, loss of BID delayed T‐cell leukemogenesis in Atm − / − mice …”
mentioning
confidence: 99%
“…The arguments regarding the mechanism by which tumor suppression is achieved in the context of ATM-loss, however, are different. 1 The authors and others have previously shown that Bid was involved in the DNA damage response. 16,17 This role of Bid has been disputed and was the subject of controversial debate 18-20 that we will not be able to resolve in this editorial.…”
mentioning
confidence: 99%
“…The patho physiologic role of apoptosis is complicated by contradictory evidences where lack of apoptosis or increased apoptosis may both result in carcinogenesis depending on the microenvironment and external influences. Our group and Qiu W, et al [41] uncovered the long term controversy on the ambivalent role of the proapoptotic BH3 only protein Bid in tumorigenesis [16,[40][41][42] and Puma in carcinogen (i.e. DEN) driven liver cancer model of mice [16].…”
Section: Puma Mediated Apoptosis Leads To Hepatic Injury and Carcinogmentioning
confidence: 99%